Моделирование продукционного процесса гороха по Украине - Иконникова, В.В. (Культура народов Причерноморья, 2013)
В работе приведены результаты численных экспериментов, дана количественная оценка влияния различных сроков сева на интенсивность фотосинтетической деятельности культуры гороха в основных природно–климатических зонах Украины. В качестве теоретической основы исследования использована динамическая модель формирования урожая сельскохозяйственных культур, адаптированная нами применительно к культуре гороха. Полученные результаты показали, что при поздних сроках сева формирование продуктивности гороха проходит при менее благоприятных агрометеорологических условиях, что приводит к значительному снижению урожая. У роботі наведені результати чисельних експериментів, дана кількісна оцінка впливу різних строків сівби на інтенсивність фотосинтетичної діяльності культури гороху в основних природно– кліматичних зонах України. В якості теоретичної основи дослідження використана динамічна модель формування врожаю сільськогосподарських культур, адаптована нами стосовно до культури гороху. Отримані результати показали, що при пізніх строках сівби формування продуктивності гороху проходить при менш сприятливих агрометеорологічних умовах, що призводить до значного зниження врожаю. The paper presents the results of numerical experiments, the quantitative estimation of the effect of different planting dates on the intensity of the photosynthetic activity of pea crops in the major climatic zones of Ukraine. As background information, we used the average regional data on a network of meteorological observations and the Hydro meteorological Service of Ukraine agro–meteorological stations. A productivity crop determined by the dynamic model is based on one hand on environmental factors, and the other – the parameters of the model. Therefore, using a dynamic model can estimate the effect of various environmental factors on crop productivity. As a theoretical basis for the study used a dynamic model of the crop, which was adapted by us in relation to the culture of peas. With the formation of the crop model to explore the photosynthetic activity of crops in different situations and different climatic zones. This may be considered a variety of combinations of parameters characterizing the growth conditions. Using the modified model were calculated key figures the rate of photosynthesis and crop yield of peas on the main climatic zones of Ukraine. As a result of the performed work we studied the effect of different planting dates on the intensity of photosynthetic activity of plants pea crops in the major climatic zones of Ukraine. The results showed that in later stages of formation productivity pea sowing extends agro under less favorable conditions, which leads to a significant reduction in yield.